The expression of MDM2, MDM4, p53 and p21 in myeloid neoplasms and the effect of MDM2/MDM4 dual inhibitor. Issue 1 (2nd January 2021) - Eskandari, Mohammad; Shi, Yang; Liu, John; Albanese, Joseph; Goel, Swati; Verma, Amit; Wang, Yanhua
Abstract: p53 together with its downstream product p21 plays an important role in tumorigenesis development. MDM2 and MDM4 are two p53 regulators. We studied the expression of p53, p21, MDM2, and MDM4 in a total of 120 cases of myeloid neoplasms including MDS, AML or MDS/MPN, and control, using single and double immunohistochemical stains. We found TP53 mutations had a worse outcome in patients with AML/MDS, and p53 expression detected by immunohistochemistry had a similar prognostic value. p21 expression was strongly related to TP53 mutation status, with loss of expression in almost all TP53 mutated cases. MDM2 and MDM4 were highly expressed in hematopoietic cells in both benign and neoplastic cells. MDM2/p53 double positive cells exceeded MDM4/p53 double positive cells in neoplastic cases. Finally, we observed that p21 protein expression was up regulated upon the use of ALRN-6924 (Aileron) while no significant changes were seen in p53, MDM2 and MDM4 expression.